Fixed drug eruption due to clarithromycin - Santoshi Balkrishna Malkarnekar; L Naveen (Wolters Kluwer Medknow Publications, 2013)
Fixed drug eruption (FDE) is an unusual adverse effect of any drug, especially antibiotics like clarithromycin. Herein we report a case of clarithromycin induced FDE in a 30-year-old man who presented with recurrent erythematous and pruritic cutaneous lesions on the lower lip, right hand and left thigh. The lesions were initially misdiagnosed as lichen planus and treated with topical steroids. Each recurrence was at the same site and the lesions faded within 2 weeks leaving behind violacceous pigmentation. All the cutaneous lesions were reproduced following an oral provocation test thus confirming the diagnosis of clarithromycin induced FDE, which is a rare occurrence. When it does occur, it is often misdiagnosed, so physicians should be aware of this condition in order to prevent future recurrences as it causes a lot of cosmetic and physical discomfort to the patient.